Tenth European Powder Diffraction Conference - Geneva, September 1-4, 2006 (Zeitschrift für Kristallographie / Supplemente, 2007)
Zeitschrift für Kristallographie. Supplement Volume 26 presents the complete Proceedings of all contributions to the X European Powder Diffraction Conference in Geneva 2006: Method Development and Application, Instrumental Software Development, Materials Supplement Series of Zeitschrift für Kristallographie publishes Proceedings and Abstracts of international conferences on the interdisciplinary field of crystallography.